PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION PADA POKOK BAHASAN BANGUN RUANG - Anggi Saputri (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2017)
This research was aimed at improvingthe students’ mathematic problem solving competencethrough Problem-Based Instruction (PBI). The subject of this research was IV graders od SD Negeri 1Kalibagor consisting of 18 males and 19 females. The design of this research was Classroom ActionResearch which was carried out in 2 cycles in which every cycle consisted of 2 meetings. In each cyclethere were planning, acting, observing, and reflecting. The result of the research indicated that theimplementation of learning mathematic through Problem- Based Instruction learning model couldenhance the mathematic problem solving competence. This was proven by the increaseof the averagescore of mathematic problem solving competence. The average score inthe first cycle was 14.21 whichwas considered goog, and in the second cycle it was 16.69 which belonged to very good criteria. Theaverage result of students’ mathematic problem soving competencetest was 71.03 in the first cycle and83.51 in the second cycle. Furthermore, the students’ learning mastery was 51.40% in the first cycleand 89.19% in the second cycle whic indicated an improvement